Revitalisasi Sistem Penyaringan Air Bersih Di Desa Gegerung Kecamatan Lingsar Kabupaten Lombok Barat - Budianto, Muh Bagus; Supriadi, Anid; Hartana, Hartana; Fajrin, Jauhar; Saidah, Humairo (Universitas Mataram, 2024)
Water is the main need for humans to fulfill life's needs. For humans, clean water is absolutely necessary for various needs, namely for bathing, washing, cooking and so on. There are several water sources that humans can use, including springs, river water and ground water. Water sourced from springs and groundwater is relatively better quality, while water sourced from rivers requires prior management. Gegerung Village is one of the villages in Lingsar District, West Lombok Regency. Some of the people of Gegerung Village depend on their water needs from the Meninting River which passes through their area. The existing water supply system is by tapping directly from the river. Before being distributed, the water first passes through a filtering system so that the water becomes clearer. However, the current condition of the water filtration system cannot function properly so that the distributed water remains dirty. To get clean water again, it is necessary to revitalize the water filtration system. Revitalization is an effort to restore the function of the water filtration system by cleaning and replacing the filter media material. The results of the tests carried out show that there is an improvement in water quality after replacing the filtering media